Monetary and fiscal policy: drivers of stability in developing economies - Hakimah, Yusro (Jurnal Konseling dan Pendidikan, 2025)
This paper investigates the role of monetary and fiscal policy in ensuring macroeconomic stability, specifically in the context of economic growth and inflation within developing countries. Using a qualitative approach, the study extensively reviews existing literature and employs library research to explore how these policies impact the economic dynamics of developing nations. The research identifies key theoretical frameworks and empirical evidence that explain the interactions between monetary and fiscal policy and their collective influence on inflation rates and economic growth. It highlights that while monetary policy, primarily through interest rates and money supply management, can influence inflation, fiscal policy via government spending and taxation—plays a crucial role in sustaining long-term economic growth. The study further explores the challenges faced by developing countries in balancing these policies, particularly in the face of external shocks and structural vulnerabilities. Through the synthesis of various studies, the paper concludes that a well-coordinated monetary and fiscal policy framework is essential for achieving macroeconomic stability. Effective coordination between these policies can mitigate inflationary pressures, promote sustainable economic growth, and enhance resilience against global economic uncertainties. The paper provides recommendations for policymakers in developing countries on optimizing these policy tools to foster economic stability and growth.